Growth and yield of juvenile fat snook at different temperatures and feeding rates - Oliveira, Luiz Augusto Altenburg Gomes; Almeida, André Marafon; Pandolfo, Pablo Seagan Vaz; Souza, Rodrigo Matos de; Fernandes, Luiz Fernando Loureiro; Gomes, Levy Carvalho (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the effects of temperature and feeding rates on growth and productivity of juvenile fat snook (Centropomus parallelus). A factorial experiment with two temperatures (25 and 28°C) and two feeding rates (3 and 6% of biomass per day) was used, with three replicates for each combination of temperature and rate. Fish (9.80±0.41 g; 9.86±0.14 cm) were fed twice a day during 60 days. Every 15 days, samples were taken to correct the amount of food offered. No mortality was observed during the experiment. A greater growth in weight and length was obtained in animals subjected to the temperature of 28°C. Weight gain, final biomass, apparent food conversion, and specific growth rate were influenced by feeding rate and temperature. The offer of 3% of biomass per day at 28°C provides better growth and productivity indices for juvenile fat snook.
Keywords: Centropomus parallelus; aquaculture; animal welfare; productive performance; water quality